Opioid use disorder during pregnancy: An overview. Issue 3 (March 2019) - Carter, Lillian C.; Read, Molly A.; Read, Laura; Nicholas, Joyce S.; Schmidt, Eric
Abstract : ABSTRACT: Women with opioid use disorder who become pregnant are a particularly vulnerable population and require a comprehensive treatment approach for mother and fetus. Research is continuing on opioid use disorder, effects of opioid use on the fetus, and best treatment approaches. This article reviews current recommendations and guidelines for treatment.